Multiple parallel twinning overgrowth in nanostructured dense cobalt ferrite. (5th November 2016) - Galizia, Pietro; Baldisserri, Carlo; Capiani, Claudio; Galassi, Carmen
Abstract: Cobalt ferrite powders were synthesized by solid state reaction of the nanosized oxides at different temperatures. The highly aggregated powders were milled, and the aggregate size was reduced from 25 – 40 μm to 12–20 μm, depending on the milling time. A correlation between milling media diameter and final granulometry, and an unexpected calcination temperature effect on the milling efficiency were found. Highly homogenous green bodies and fully dense materials were produced for the first time after conventional sintering. The crystallite size depends primarily on the heating conditions and decreases from 50 – 70 nm to 27–13 nm. Under the same sintering conditions, particle morphology and crystallite size control the final grain shape, producing twinned grains with increased multiple parallel twinning overgrowth for the finer powders. The sintered cobalt ferrite ceramics show a relative density of 96–99%. The higher the planar faults density and grain size, the lower is the induced magnetization due to increased domain walls pinning. The variation of initial susceptibility was explained by extending the Globus model to the case where the domain walls are pinned at twinning boundaries. A linear correlation between multiparallel-twinned grains fraction and initial susceptibility was found. Graphical abstract: Highlights: Fully dense (96-99%) cobalt ferrite was produced with tailored microstructure by design of calcination and milling treatments Grain growth by multiple parallel twinning leads to nanostructured crystals assembly depending on starting crystallite size The extension of the Globus model accounts for the influence of twin boundaries on the initial susceptibility.